Optimization of Centrifugation Speed and pH in Extraction of Uricase Enzyme from Goat Liver - Handayani, Wuryanti; Esti Utarti; Riki Juni Krismiadi; AA. Istri Ratnadewi (Indonesian Chimica Letters, 2022)
The human body does not have an enzyme that can break down uric acid, so the accumulation of uric acid can cause disease. This problem can be overcome by uricolytic therapy by utilizing the activity of the uricase enzyme. In this study, the uricase enzyme was extracted from goat liver by optimizing the centrifugation speed and the extraction pH. The purpose of the optimization is to get maximum uricase activity. Uricase extraction to optimize centrifugation speed using borate buffer pH 8.5 then centrifuged at 7.000; 9.000; 11.000; 13.000 and 15.000 rpm with a temperature of 4oC. Furthermore, pH optimization was carried out using pH buffers 6, 7, 8, 9, 10 and 11 by centrifuging the optimum speed obtained. The crude extract obtained was further tested for its enzyme activity . The results showed that the highest uricase activity was achieved if the extraction was carried out at pH 8 using centrifugation at an optimum speed of 13,000 rpm. The higher uricase activity indicates that the extracted uricase concentration is increasing.